Local Entrepreneurship Platform: Community Center Design for Independent Garífuna Mothers in Tornabé - Ochoa Perdomo, Valery Anayansi; Flores, Cinthia; Inestroza Lozano, Demmi Paola (LACCEI, 2025)
This article presents the research for the architectural design of an intercultural community center focused on the empowerment of Garífuna women, specifically independent mothers from the community of Tornabé, Honduras. The objective was to generate a design proposal that articulates gender needs, local entrepreneurship, and territorial sustainability through a participatory approach. A mixed-methods methodology was applied, combining qualitative and quantitative techniques: documentary analysis of 79 sources, semi-structured interviews with women leaders from the “Mariposas Libres” organization, structured surveys of 30 potential users, field visits with on-site recognition, and participant observation. An expert judgment technique was used to validate the proposed architectural program. Findings show that Garífuna women face structural barriers in accessing adequate spaces for training, production, and community organization. Participants expressed aspirations related to economic autonomy, technical education, and cultural strengthening. Based on these insights, a 976.34 m2 center was designed, distributed into two functional modules with an estimated budget of USD 607,552.49. The project incorporates principles of bioclimatic architecture, use of local materials, and design adapted to care and productive dynamics. It is concluded that architectural design can become a platform to foster community entrepreneurship led by women, establishing a replicable model of infrastructure with a gender-sensitive and culturally relevant approach.